Analysis of the Abscopal Effect With Anti-PD1 Therapy in Patients With Metastatic Solid Tumors. Issue 9 (November 2016) - Ribeiro Gomes, Jéssica; Schmerling, Rafael A.; Haddad, Carolina K.; Racy, Douglas J.; Ferrigno, Robson; Gil, Erlon; Zanuncio, Pedro; Buzaid, Antônio C.
Abstract : Abscopal effect is a rare phenomenon characterized by tumor regression of untreated metastatic lesions after a local therapy (eg, radiotherapy). We studied the probability of abscopal effect with radiotherapy associated with anti-programmed death cell 1 (PD1) therapy after progression on anti-PD1. This study is a retrospective analysis of patients treated with nivolumab or pembrolizumab for melanoma, non–small cell lung cancer (NSCLC) and renal cancer at Antônio Ermírio de Moraes Oncology Center, Brazil. To be eligible for this analysis, patients must have had unequivocal evidence of disease progression on anti-PD1 therapy and subsequent radiotherapy for any tumor site while still receiving anti-PD1. The abscopal effect was characterized as a response outside the irradiated field after radiotherapy plus anti-PD1. Sixteen patients were evaluated, including 12 metastatic melanoma, 2 metastatic NSCLC, and 2 metastatic renal cell carcinoma. The median time to disease progression on anti-PD1 was 3 months. The radiotherapy field included lung, lymph nodes, and bones, with a median total dose of 24 Gy (1–40 Gy), usually in 3 fractions (1–10 fractions). Three patients with melanoma developed an abscopal effect at a rate of 18.7% (25% among melanoma patients). Of note, one of them achieved a remarkable complete response lasting >6 months. Three patients with melanoma obtained a significant local response after radiotherapy, despite no response in distant metastases. Eleven patients presented disease progression after radiotherapy. No increased toxicity was observed. In conclusion, no patients with NSCLC or renal cancer showed abscopal effect, but 25% of patients with melanoma showed regression of nonirradiated lesions when anti-PD1 was continued after radiation to a tumor site that had progressed on anti-PD1 monotherapy.